Higher Ultra-Processed Food Consumption is Associated with Increased Risk of Mental Health Issues in Undergraduates - Sazali, Azira; Yusoff, Nur Atikah; Azmawi, Nadya Insyirah; Li, Ng Ming; Yahya, Hanis Mastura; Yaacob, Norhasniza; Malek Rivan, Nurul Fatin (Jurnal Gizi dan Pangan, 2025)
This cross-sectional study, involving 250 healthy undergraduate students, aimed to examine the association between Ultra-Processed Food (UPF) consumption and mental health status. Mental health was assessed using the 12-Item General Health Questionnaire (GHQ-12), where participants were classified as either normal or high-risk based on their scores. Subsequently, dietary intake was assessed using the Dietary History Questionnaire (DHQ), examining meals throughout the day. Additionally, the degree of food processing was classified using the NOVA food classification. Univariate and multivariate logistic regression analyses were used to evaluate the relationship between mental health status, ultra-processed food consumption, and the contributing factors. The average daily energy intake was 1,216±488 kcal, with 25.7% coming from ultra-processed foods. Those at higher risk for mental health issues typically had a slightly lower fat percentage (26.5±8.5%) but a higher total body water percentage (50.6±4.7%) compared to those with normal mental health. Even after adjustment for confounding factors, high consumption of ultra-processed foods remained strongly associated with an increased risk of mental health problems (OR=2.196, 95% CI:1.056–4.566, p=0.035). Further research is needed to fully understand the effects of ultra-processed foods on mental health and enhance awareness of their risks while promoting fresh, minimally processed alternatives.